109 ESC risk score-adjusted cost analysis of the investigations in stable chest pain: NICE vs. ESC guidelines. (May 2019) - Papachristidis, Alexandros; Denny, Sarah; Vaughan, George; Akbari, Tamim; Avornyo, Edith; Griffiths, Tracey; Saunders, Emma; Byrne, Jonathan; Monaghan, Mark; Alfakih, Khaled
Abstract : Introduction: National Institute for Health and Clinical Excellence (NICE) have removed the use of pre-test probability risk score (RS) in patients with new onset stable chest pain. They recommend computed tomography coronary angiography (CTCA) as first line investigation irrespective of RS. European Society of Cardiology (ESC) suggest using the ESC RS and recommend functional tests as initial investigation in patients with RS 15–85% and allow for the use of CTCA in patients with RS of 15–50%. We compare the two recommended strategies (NICE vs ESC) as applied in two neighbouring NHS Trusts in South London. We additionally investigate the prognostic role of ESC RS in terms of need for revascularization. Methods: Two groups of patients, who attended rapid access chest pain clinics in two neighbouring NHS Trusts were recruited. Group A (N = 667) were investigated based on ESC guidelines, whereas Group B (N = 654) were investigated following NICE guidance. The RS was calculated as per ESC recommendation based on patient age, gender and typicality of chest pain. The patients were divided in two subgroups according to ESC RS. Sub-groups A1 and B1, were of patients with lower RS (15–50%) and sub-groups A2 and B2 were of patients with higher RS (>50%). The need for invasive coronary angiography (ICA) and revascularization were compered between groups and sub-groups. A cost analysis was performed based on UK tariffs for CTCA (£220), stress echo (£176) and ICA (£1, 001). Results: Baseline characteristics and the prevalence of cardiovascular risk factors were similar between Groups A and B (table 1 ). The rate of progression to ICA was comparable in the two groups (9.9% vs 12.0%; p=0.377), as was the rate of revascularization (4.0% vs 5.0%; p=0.532) (Figure 1 ). The average per investigated patient cost was lower in Group A by £46.11 (£279.66 vs £325.77). In Group A1 there was a lower rate of progression to ICA compared to Group B1 (8.7% vs 12.6%, p=0.177) as was for revascularization (2.6% vs 5.5%, p=0.122). The average per patient cost was considerably lower in Group A1 by £69.54. 18.5% of patients proceeded to ICA in Group A2 compared to 14.6% in Group B2 (p=0.512) and 10.8% were revascularized as opposed to 5.2% (p=0.187). The average cost per investigated patient was slightly higher in Group A2 by £20.99. Investigating possible predictors of revascularization (ESC RS, diabetes, family history of coronary artery disease, smoking, hypercholesterolaemia), only the ESC RS was found to be independently related to the need for revascularization (OR: 1.049, 95%CI: 1.036–1.062, p<0.001). Conclusion: Both NICE and ESC recommendations on new onset stable chest pain lead to similar rates of progression to ICA and revascularization, but lower cost when stress echo (ESC guidance) is used as first line investigation. There was no significant difference when we repeated the analysis in low and high ESC RS patients. However, the ESC RS was the only independent predictor of need for revascularization. Conflict of Interest: None